Effect of Leaves and Stems Extract of Ciplukan (Physalis Angulata L.) on The Severity of Steatosis in Wistar Rat Liver Induced by Egg Yolk and Propylthiouracil - Adi Nugraha; Ety Sari Handayani; Dewa Nyoman Murti Adyaksa; Miranti Dewi Pramaningtyas (Biomedika, 2025)
The increasing habit of consuming high-fat foods and a sedentary lifestyle increases the incidence of hepatic steatosis. There are currently no approved medical drugs to prevent and treat steatosis. The leaves and stems of the ciplukan plant (Physalis Angulata (L.)) are rich in flavonoid compounds and phenolic acids which have preventive and curative effects on steatosis. This research aimed to determine the impact of ciplukan leaves and stems extract on the severity of steatosis in the liver of Wistar rats induced by egg yolk and propylthiouracil. This research consisted of four groups: first group induced by egg yolk and propylthiouracil for six weeks (n=7), second group induced egg yolk and propylthiouracil plus simvastatin 0.18 mg/200 gBW for six weeks (n=7), third group induced by egg yolk and propylthiouracil plus ciplukan extract 400 mg/kgBW for six weeks (n=7), fourth group induced by egg yolk and propylthiouracil plus ciplukan extract 800 mg/kgBW for six weeks (n=7). The severity of steatosis was determined based on histopathological observations by an anatomical pathology specialist. The first group had four preparations with moderate degree of steatosis. The second group had three preparations with moderate degree of steatosis. The third group had two preparations with moderate degree of steatosis. The fourth group had two preparations with moderate degree of steatosis. The statistical test results showed no significant difference in severity between the treatment groups (p=0.692). The administration of ciplukan leaves and stems extract can prevent a decrease in high-density lipoprotein levels in Wistar rats induced by egg yolk and propylthiouracil. However, no significant influence was found on the severity of hepatic steatosis.